2021
DOI: 10.1249/01.mss.0000763200.89203.59
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Social Distancing During Covid-19 On Psychological Mood And Physical Activity

Abstract: The COVID-19 pandemic cause many locales to implement social distancing or social isolation policies to slow the transmission of the disease. Social distancing has previously been shown to contribute to poor mental health and reduced participation in physical activity. On-going isolation can lead individuals to feel detachment from others, feeling uncertain about the future, boredom, and loss of freedom. PURPOSE:The purpose of the present study was to examine self-reported psychological mood and physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many governments provided free COVID-19 testing to the public, including large-scale community-based testing (e.g., China) ( 5 , 6 ). Such preventive measures involved extremely high social, psychological, and economic costs ( 7 , 8 ). A balance between control versus costs was difficult to achieve and often politicized ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many governments provided free COVID-19 testing to the public, including large-scale community-based testing (e.g., China) ( 5 , 6 ). Such preventive measures involved extremely high social, psychological, and economic costs ( 7 , 8 ). A balance between control versus costs was difficult to achieve and often politicized ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In addition, many BSMM access PrEP through community-based services that often rely on strong social networks; these networks may be weakened given the increased distancing and isolation presented by the pandemic. 24,25 Distrust in health care systems and discrimination were exacerbated during the pandemic; these are welldocumented barriers to PrEP use. 15,26,27 As an effective strategy for HIV prevention, PrEP use is critically relevant for BSMM, who are substantially more vulnerable to HIV acquisition than their white or heterosexual peers.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies clarify how eating-related factors impact affect and subsequently contribute to LOCE, they do not address how other day-to-day factors outside of eating may also be contributing. Research outside of the eating disorder (ED) field has found that non-eating activities including cooking [ 20 ], indoor hobbies {e.g., reading [ 21 ], digital gaming [ 22 ]}, outdoor recreation [ 23 , 24 ], socializing [ 25 ], and meditation [ 26 , 27 ] improve affect, while watching TV [ 21 ], driving [ 28 ], and napping [ 29 , 30 ] worsen or have a mixed impact on affect. However, these studies primarily utilized retrospective recall of non-eating activity engagement and affect which allows for recall error.…”
Section: Introductionmentioning
confidence: 99%